Eritrea : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1996)
This paper describes economic developments and reforms in Eritrea during the 1990s. The paper highlights that the government's main economic objectives were to promote high and sustainable economic growth and thereby increase per capita income, create employment opportunities, and attain a sustainable external position over the medium term. The paper discusses the developments in domestic production, prices, and the structural reforms undertaken in Eritrea. Developments in public sector finances are covered, and monetary developments and financial sector reform efforts are also summarized.